A Study on the Relationship of Personality Traits with Happiness of Students (International Journal of Innovative Research in Engineering & Management, 2021)
Happiness is a mental state that results from fulfilling one's  goals. Happiness has risen to prominence as one of the most  significant indicators of societal advancement. Happiness has  now established itself as one of the most important indices of  societal progress. The significance of happiness is magnified  by two when it comes to university students. All personality  traits and happiness have a significant connection, according to  the research. Extraversion has the strongest relationship to  happiness, followed by neuroticism. The impact of gender on  happiness has been studied, and the findings reveal that there is  no vital variance between male or female student happiness  levels, despite the fact that male students are happier on  average. Male students are happier than female students,  according to happiness statistics from undergraduates,  graduates, and postgraduate students. The main purpose of this  research is to examine the influence of happiness on student  happiness as well as to compare the happiness levels of male  and female students. Several studies have been conducted in  this area, but more will be required in the future.
Keywords: Graduate; Happiness; Post Graduate; Personality; Students; Under Graduate